Development of a Kodular-Based Learning Media Application for Qur’an and Sunnah Material - Rifda Rizky Aulia; Abdul Azis; Setria Utama Rizal (STAI Syaichona Moh. Cholil Bangkalan, 2025)
This study aims to develop and validate an Android-based learning media application, utilizing the Kodular platform, for Islamic Religious Education (PAI) focusing on Qur’an and Sunnah material. The application is designed as a learning guideline for grade VII students at SMPN 1 Palangka Raya. Employing the 4D development model (Define, Design, Develop, Disseminate), the research encompassed needs analysis, product design, iterative development, and validation stages. The developed application integrates interactive content, educational videos, and assessment quizzes. Validation by media experts yielded a very feasible score of 98.43%, while content experts rated it 80.77% feasible. Subsequent small-scale and large-scale field trials with students confirmed positive responses, achieving feasibility scores of 81.84% and 88.54% respectively. These findings indicate that the Kodular-based learning application is highly feasible, effective, and suitable for enhancing students' engagement and ability to read the Qur’an with proper tajweed. This media innovation offers a promising, accessible, and engaging solution to improve Islamic Religious Education delivery at the junior high school level.